A study on Human Resource Management Processes and Practices- A Review (International Journal of Scientific Research and Management (IJSRM), 2016)
The most important asset for any organization is their Human Resources and they serve the organisation to achieve its goal. Management of human resources plays an extremely vital role as compared to the technology or capital and for its effective management, organization requires effective HRM practices. HRM practices refer to activities of organization directed at managing the puddle of human resources and ensuring that the resources are engaged towards the accomplishment of organizational goal. This paper has been designed to review the existing literature based on HRM Practices. The purpose of this paper is to build up an understanding of HRM Practices and to examine the unique HRM practices implemented by different organisations. After reviewing the existing literature on HRM practices, the researchers have established that the external as well as internal factors affect the HRM practices which leads to direct or indirect effect on other variables such as employee’s attitude, employee employer relations, financial performance, employee productivity etc. and ultimately contribute to overall corporate performance. On the basis of the literature reviewed, a normative skeleton has been developed that shows how HRM practices leads to overall corporate performance